Proceedings of the 12th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2006
DOI: 10.1145/1150402.1150492
|View full text |Cite
|
Sign up to set email alerts
|

Combining linguistic and statistical analysis to extract relations from web documents

Abstract: The World Wide Web provides a nearly endless source of knowledge, which is mostly given in natural language. A first step towards exploiting this data automatically could be to extract pairs of a given semantic relation from text documents -for example all pairs of a person and her birthdate. One strategy for this task is to find text patterns that express the semantic relation, to generalize these patterns, and to apply them to a corpus to find new pairs. In this paper, we show that this approach profits sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 20 publications
1
71
0
2
Order By: Relevance
“…The outcome is used to enrich the knowledge base. So far, a variety of tools working in this scheme have been proposed, including Snowball [30], Semagix/SWETO [31], KnowItAll [32], Text2Onto [33], LEILA [34], TextRunner [35], and SEAL [36]. These systems also take advantage of natural language processing tools to improve the results by employing parts-of-speech tagging, lexical dependency parsing or using heuristics for entity disambiguation, etc.…”
Section: Related Workmentioning
confidence: 99%
“…The outcome is used to enrich the knowledge base. So far, a variety of tools working in this scheme have been proposed, including Snowball [30], Semagix/SWETO [31], KnowItAll [32], Text2Onto [33], LEILA [34], TextRunner [35], and SEAL [36]. These systems also take advantage of natural language processing tools to improve the results by employing parts-of-speech tagging, lexical dependency parsing or using heuristics for entity disambiguation, etc.…”
Section: Related Workmentioning
confidence: 99%
“…The benefit of using LGP is that there exists a structure similarity to CGs, hence it is easier to map the obtained structure to CGs [26]. Suchanek et al [27] reported that the LGP provides a much deeper semantic structure than the standard context-free parsers. The parser is able to identify the syntactic level of sentence decomposition and categorizes the phrase into the following: S, which represents sentences; NP, which represents Noun Phrases; VP, which represents Verb Phrases; and PP, which represents Preposition Phrases.…”
Section: Parsing and Conceptual Graph Generationmentioning
confidence: 99%
“…LEILA [18] automatically generated negative examples using information about the cardinality of relations. Work conducted in [19] [20] employed semi-supervised learning algorithms and achieved good performance using only a small amount of labeled examples.…”
Section: Related Workmentioning
confidence: 99%